Strategi Internalisasi Nilai-Nilai Sipakatau’ dan Implikasinya Terhadap Perilaku Belajar Peserta Didik MTs Nuhiyah Pambusuang Kecamatan Balanipa Kab. Polewali Mandar - Jamaluddin (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
This study aims to carry out the process of implementing classroom actions through the internalization strategy of sipakatau values ​​and to describe the internalization strategy in terms of procedures and implications for the learning behavior of students at MTs Nuhiyah Pambusuang. Disclosure of the problems studied, the researchers used a CAR research approach in collaboration with descriptive qualitative research with classroom action design and field reality through observations and interviews. The research location is MTs Nuhiyah Pambusuang which is located on the Makassar KM axis road. 285 Pambusunag, Pambsuuang village, Balanipa sub-district, Polewali Mandar district. The data sources in this study were 1 principal, 4 vice principals, 1 administrative staff, and 4 teachers. The results of data analysis show that the strategy of internalizing sipakatau' values ​​can change the learning behavior of MTs Nuhiyah Pambusuang students with facts and realities in the field. The results of research on the implications of internalizing sipakatau' values ​​on students' learning behavior, namely: (1) Sipakata' values ​​in the social life of MTs Nuhiyah Pambusuang students by seeking several things, namely: a. Giving Mitabe's Advice, b. Restrictions on the use of mobile phones, c. Mulok Maple Adjustment. (2) Strategy for Internalizing Sipakatau' Values ​​Against Students of MTs Nuhiyah Pambusuang, namely: a. Procedures for internalizing sipakatau' values ​​include: (a) Value internalization stage, (b) Value transaction stage, (c) Trans-internalization stage. b. The Strategy for Internalization of Sipakatau's Values ​​taught in Class VII A of MTs Nuhiyah Pambusuang, namely: (a) In class, namely during the learning process, (b) Outside class, namely: 1) Reward and Punishment, 2) Through association, 3) Through giving role models, 4) Through habituation, 5) Through giving advice, 6) Through discussion and question and answer, 7) Through the rules made by the madrasa, and 8) Creating a sipakata' atmosphere in the madrasa. c. Implications of Internalization of Sipakatau's Values ​​on the Behavior of MTs Nuhiyah Pambusuang Students. The four indicators are as follows: 1) Students respect each other, 2) Politeness in acting, 3) Students are sympathetic and caring, and 4) KKM scores are above average.